Spot's nature fun : a peep-through book - Eric Hill (London; Puffin Books, 2023)
Join Spot and Grandma as they go on a walk together, finding lots of lovely nature sounds along the way. Look behind the peekaboo flap on every page to discover the hidden surprises!
Keywords: Picture books